Influence of Compensation, Leadership Style, and Work Culture on Work Effectiveness at Youth, Sports, and Tourism Office of Cilegon City - Yuliana, Nuni Malihatun; Imron, Ali; Wirtadipura, Dian; Chaidir, John; Ali Imron (Journal of Business Management and Economic Development, 2025)
The purpose of this study was to examine and analyze the influence of compensation, leadership style, and work culture on employee work effectiveness at the Youth, Sports, and Tourism Office of Cilegon City. This research was conducted at the Youth, Sports, and Tourism Office of Cilegon City using a descriptive quantitative method with data collection through questionnaires. The respondents in this study were employees of the Youth, Sports, and Tourism Office of Cilegon City, determined using a saturated sampling method with a total of 94 respondents. Data were collected through questionnaires using a 1–5 Likert scale, and data analysis employed multiple linear regression with the assistance of SPSS version 25 software. The results of the study and hypothesis testing indicate that: (1) Compensation has a positive and significant effect on work effectiveness; (2) Leadership style does not have a positive and significant effect on work effectiveness; (3) Work culture has a positive and significant effect on work effectiveness; and (4) Simultaneously, compensation, leadership style, and work culture have a strong and significant influence on employee work effectiveness.